An Examination of Social Anxiety in Marijuana and Cigarette Use Motives Among Adolescents. (23rd February 2016) - Cloutier, Renee M.; Blumenthal, Heidemarie; Mischel, Emily R.
ABSTRACT: Marijuana and nicotine are two of the most widely used substances among adolescents in the United States. Symptoms of social anxiety (SA) typically emerge during early adolescence, and elevated levels are associated with increased substance-related problems despite inconsistent links to frequency of use. Substance use motives, and in particular coping motives, have been found to play an important role in understanding the heightened risk for use problems among those with elevated SA. Importantly, work to date has been conducted almost exclusively with adult samples; thus the current study examined whether similar patterns would emerge among adolescents. The current project included 56 community-recruited adolescents (ages 12–17 years; 41% girls) with a positive history of lifetime marijuana and cigarette use. Consistent with the adult literature, SA was not positively associated with frequency of use across either substance. Further, SA was positively associated with conformity use motives and unrelated to social or enhancement motives for both substances. Unexpectedly, SA was unrelated to coping use motives for either marijuana or cigarettes. These preliminary data highlight the need for future research designed to forward developmentally sensitive models of substance use behaviors and etiology.